ANALYSIS AND FORECASTING OF CONSEQUENCES PERTAINING TO PRICE CHANGES ON IMPORTED NATURAL GAS BY POWER-GENERATING ENTERPRISES OF THE REPUBLIC OF BELARUS - M. P. Kondratiev; S. A. Kirinovich (Наука и техника)
The analysis of consequences of price changes for imported natural gas used at enterprises involved in energy generation has been carried out by example of one of Belarusian regional power supply systems.The offers for maximum compensation of economic losses at the expense of price increase for the gas supplied by Russia have been proposed in the paper.